Physicochemical Properties, Lipid and Fatty Acid Profile of “Batuan” [Garcinia binucao (Blco.) Choisy] Seed Oil - Quevedo, Elizabeth S.; Pham, Laura J.; Merca, Florinia E.; Laurena, Antonio C. (Annals of Tropical Research, 2015)
The seed oil of “batuan” [Garcinia binucao (Blco.) Choisy] fruit, an indigenous, lesser known, and with promising economic potential, was characterized to evaluate its quality and potential for product development. Using standard AOAC methods, thin layer chromatography and gas chromatography, the physicochemical properties, lipid and fatty acid profile were determined. Oil yield from “batuan” seeds was high. The extracted oil was yellowish white, soft solid at room temperature. Iodine value, acid value, and peroxide value of the seed oil were low while saponification value was high. Lipid presents in “batuan” seed oil is mostly triglycerides while diglycerides are in low amount. Unsaponifiable matter (<1.0%) was abundant in sterol, squalene and beta-carotene, and minor amount of Vit. A palmitate, – and -tocopherols. Stearic (C18:0), oleic (C18:1), and palmitic (C16:0) acids were the major fatty acids while arachidic, linoleic and linolenic acids constitute the minor components. “Batuan” seed oil contained more saturated fatty acids than the unsaturated fatty acids which could be responsible for its being a soft solid at room temperature. Results of this study show that “batuan” seed oil is of good quality and could be a potential source of valuable oil for food and other industrial applications.